University Efforts for Quality to Ensure Epistemological Access - Irfana Omar; Muhammad Shahzad Chaudhry (University of Management and Technology, 2019)
The purpose of this study is to explore the existing relationship among the quality of university efforts (teacher efforts and management efforts), the willingness of students to learn and customer satisfaction in order to ensure epistemological access to higher education in private universities of Pakistan. For this purpose, a survey was conducted with 339 students studying in three different faculties of a private university. It was aimed to collect their responses regarding their experiences at the campus about purposeful access to available resources and to measure their satisfaction level with the provided access. The data was collected through multistage sampling. It was found that there is a positive correlation among teacher efforts for epistemological access (TEEA), management efforts for epistemological access (MEEA), and customer satisfaction (CS); whereas, TEEA, MEEA, and CS are negatively correlated with student willingness (SW). It was also found that SW does not act as a mediator between UEQ and CS. The study contributes in the existing literature by accentuating the need for epistemological access by enhancing the willingness of students to learn and by providing quality university efforts to translate academic experiences into successful opportunities in the future.